2018
DOI: 10.1590/s1984-296120180041
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of Cassia fistula and Combretum leprosum protein fractions against goat gastrointestinal nematodes

Abstract: In this study, we evaluated the ovicidal and larvicidal activity of protein preparations obtained from Cassia fistula L. and Combretum leprosum Mart. leaves on the gastrointestinal parasites of goats. Protein preparations were obtained after the extraction of C. fistula L. and C. leprosum Mart. leaves, followed by protein fractionation (with ammonium sulfate saturation percentages of 30%, 30%-60%, and 60%-90%) and dialysis, which resulted in protein fractions (called F1, F2, and F3, respectively). The fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Tannins may affect via two mechanisms; the first is direct, which may be done by altering biological processes inside nematode (Hoste et al, 2006), the second effective mechanism may be done indirectly through the inhibition of egg hatching (Butter et al, 2000). The larvicidal action observed by C. fistula protein preparations may be related to the presence of lectins, the larvicidal action is genuine to this class of proteins (Silva et al, 2018). It was suggested that the adverse effect of Cassia alata against nematodes may linked to the presence of saponins, which in the extract, and it may also be related to the ability of saponins to disrupt eggs membranes and to increase their permeability, thus countering egg maturation (Mansfield et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tannins may affect via two mechanisms; the first is direct, which may be done by altering biological processes inside nematode (Hoste et al, 2006), the second effective mechanism may be done indirectly through the inhibition of egg hatching (Butter et al, 2000). The larvicidal action observed by C. fistula protein preparations may be related to the presence of lectins, the larvicidal action is genuine to this class of proteins (Silva et al, 2018). It was suggested that the adverse effect of Cassia alata against nematodes may linked to the presence of saponins, which in the extract, and it may also be related to the ability of saponins to disrupt eggs membranes and to increase their permeability, thus countering egg maturation (Mansfield et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Leaves and stem bark extracts were found to have various activities including antipyretic, anthelmintic, antidiabetic, protective, antioxidant, antiulcer, antitumor and antimicrobial activities etc., Extracts of the plant showed its effect against constipation, piles and also it is considered to be a detoxifier. Anthelminthic potential of C. fstula was previously reported also, in this regard, Silva et al (2018) assessed the larvicidal and ovicidal activity of protein preparations obtained from Cassia fstula leaves on the gastrointestinal parasites of goats. Cassia fistula pod extract' showed anthelmintic potential, eggs hatching inhibition, and larval mortality were observed also on gastrointestinal nematodes of sheeps (Zaragoza-Bastida et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation